Experimentação com arduino para a compreensão de circuito elétricos. - SANTOS, Danilo Antônio Barra dos (2024)
In this work, the main objective is to explain how Ohm's law is related to electrical circuits. And how this law can explain the differences in experimental results between circuits with resistors in series and in parallel. For the development of the main project, several components are used to assemble the circuits, among them is the Arduino UNO prototyping board, which will be used to program the circuit of the pushbutton experiment. In CHAPTER 1, the work aims to explain the basic concepts of electrical circuits, in addition to explaining the function of each component, along with the physical concepts that guide them. In CHAPTER 2, the focus is directly linked to the experiment itself, and to the processes of assembling the circuits, both in series and in parallel. Virtual circuits that illustrate the real experiment are presented in parallel, in order to facilitate the visualization and understanding of the process of assembling the circuits. A virtual resource used in this work, for this purpose, is Thinkercad, which works as a virtual bench for an electronic laboratory. Understanding the assembly of the circuits and the function of each component, it is possible to carry out the experimental measurements and relate them to the theoretical results. Thus obtaining results that can be explained and validated by Ohm's law.